Prevalence of gestational diabetes mellitus and associated factors in Southern Ethiopia - Woticha, Eskinder Wolka; Deressa, Wakgari; Reja, Ahmed (Asian Journal of Medical Sciences, 2018)
Background: Presence of gestational diabetes mellitus during pregnancy has serious complications for both mother and child. Its burden is increasing in low and middle-income countries but, little is known about its contribution in Ethiopia. Aims and Objective: The aim of this study was to determine the prevalence of gestational diabetes mellitus and to identify associated factors in Wolaita Zone, Southern Ethiopia. Materials and Methods: Institution based cross sectional study was carried out from August 2017 to October 2017 in Wolaita Zone, southern Ethiopia. A total of 518 pregnant women were participated from 2 hospitals and 4 health centers. Capillary blood samples were collected at fasting and 2 hours after 75gm glucose load to measure blood sugar and diagnosis of gestational diabetes mellitus was made by using 2013 World Health Organization (WHO) criteria. Binary logistic regression model was applied to assess risk factors of gestational diabetes mellitus. Results: Prevalence of gestational diabetes mellitus was 4.2% (95% CI, 2.5, 6.2) with mean post glucose load level of 160.1 mg/dl (6.3) and 15(4%) among urban residents and 7(4.9%) among rural residents. The proportion of gestational diabetes mellitus increases with increase in number of pregnancies. Previous history of spontaneous abortion (AOR: 3.5; 95%CI: 1.7-14.6), family history of type II diabetes (AOR: 4.3; 95%CI: 1.3-8.7) and previous caesarean section (AOR: 7.5; 95%CI: 1.3-14.4) were found to be significantly associated with gestational diabetes mellitus. Conclusions: The prevalence of gestational diabetes mellitus is higher as compared to other studies conducted in the country. Strengthening screening, care and prevention strategies for gestational diabetes mellitus are important to improve maternal and child health.